MACROECONOMIC VARIABLES ANALYSIS (INFLATION AND BI 7-DAY REVERSE REPO RATE) ON SHARIA BANKING FINANCING IN INDONESIA - Haq, Furqonul; Fitrianto, Fitrianto; Yusfiarto, Rizaldi (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2021)
ABSTRACTMacroeconomic variables are numerous, including inflation and interest rates determined by the central bank. The interest rate determined by Bank Indonesia is called the BI 7-Day (Reverse) Repo Rate. Inflation and BI 7-Day (Reverse) Repo Rate in the world of sharia banking in Indonesia are two important things that are always taken into account in carrying out the function of banks as a channel of financing to the public. It can be said that sharia banking financing directly or indirectly is greatly influenced by inflation and the BI 7-Day (Reverse) Repo Rate. To calculate the effect of inflation and BI 7-Day (Reverse) Repo Rate on sharia banking financing, this study was conducted. The data used in this study are inflation data, BI 7-Day (Reverse) Repo Rate and sharia banking financing on a monthly basis from 2010-2019 (120 months). The data is then processed by the statistic method using SPSS software with the t test and F test using. The independent variables used in this research are Inflation and BI 7-Day (Reverse) Repo Rate. Hypothesis testing shows that inflation has no significant effect on Islamic banking financing in Indonesia. Meanwhile, the BI 7-Day (Reverse) Repo Rate variable has a significant effect on Islamic banking financing in Indonesia. The results of the F test show that the inflation variable and the BI 7- Day (Reserve) Repo Rate simultaneously have an influence on Islamic banking financing in Indonesia.Keywords: Infation, BI 7-Day Reverse Repo Rate, Sharia Banking Financing